COVID-19 Impact on Community-Based Homestay Tourism Villages in the Annapurna Conservation Area - Dahal, Sangita; Khatiwada, Shreekanta S.; Timilsina, Yajna Prasad (Journal of Forest and Natural Resource Management, 2024)
Community-based homestay tourism program is one of the recently growing rural tourism enterprises in Nepal. It has been regarded as economic chain for upgrading rural livelihood in several parts of Nepal, preferably in nearby location of popular tourist destinations, which strongly support ecotourism and rural development. The outbroke of COVID-19 developed a global shock and damaged the tourism sector of globe including Nepal. The pause of tourism activities and halt of traveler’s movement had increased crisis in the tourism sector of the country as well as local level, interrupting the economic aspect of whole nation. This study analyzed the impact of COVID-19 lockdown on ecotourism in conservation area, particularly in homestay tourism villages of Machhapuchhre Rural Municipality of Kaski district, Nepal by collecting household level data from 40 households. The study further analyzed the positive and negative effects of lockdown in economic, environmental and socio-cultural aspects of homestay tourism. COVID 19 had constructively impacted on the environment sector by proper solid waste management and less fuel wood consumption but negatively impacted on economic and socio-cultural aspect of homestay tourism, which caused reductions in income, visitors flow and employment. Hence, we need to adopt supporting strategy to promote community-based homestay tourism by the government.